2019
DOI: 10.1080/02670836.2018.1550864
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and tensile properties of a 0.20C4.86Mn steel after short intercritical-annealing times

Abstract: This work studies the microstructure and tensile properties of a cold-rolled Fe–0.20C–4.86Mn (mass %) steel after short intercritical annealing (IA) times using scanning and transmission electron microscopy, and uniaxial tensile tests. The short IA time is applied to represent the process characteristics of the industrial continuous annealing line. The experimental results show that IA temperature has a strong influence on the final microstructure and tensile properties while IA time has less. The fractions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…Martensite transformation occurred in A740-A755 steels, while no martensite transformation was observed in A680-A725 steels. These results indicated that thermal stability of intercritical austenite is significantly influenced by IA temperature, which is similar to the result in previous medium-Mn steels, such as in cold-rolled Fe-0.3C-6Mn steel [26], Fe-0.20C-4.86Mn steel [27] and Fe-0.05C-12Mn-3Al steel [28]. Different IA temperature results in different concentration of alloying elements in the intercritical austenite due to elemental partitioning between intercritical austenite and ferrite [29,30].…”
Section: Thermal Stability Of Intercritical Austenitesupporting
confidence: 89%
“…Martensite transformation occurred in A740-A755 steels, while no martensite transformation was observed in A680-A725 steels. These results indicated that thermal stability of intercritical austenite is significantly influenced by IA temperature, which is similar to the result in previous medium-Mn steels, such as in cold-rolled Fe-0.3C-6Mn steel [26], Fe-0.20C-4.86Mn steel [27] and Fe-0.05C-12Mn-3Al steel [28]. Different IA temperature results in different concentration of alloying elements in the intercritical austenite due to elemental partitioning between intercritical austenite and ferrite [29,30].…”
Section: Thermal Stability Of Intercritical Austenitesupporting
confidence: 89%
“…Considering weldability, the content of Carbon (C) used in the steel sheets kept under scrutiny lies in the range of low-carbon steels [30]. A typical Mn content for medium Mn steels [3] has also been considered in this experiment. Cr and B have been added to improve the hardenability and strength [31], and Si (1 wt-%) was added to provide appropriate final surface conditions by applying surface processes [1].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, medium Mn steels (3-10 wt-% Mn) have been considered new candidates for the third-generation advanced high-strength steels (AHSSs) [1][2][3][4][5]. Weight reduction [6][7][8], fuel efficiency [9], passengers' safety [10,11] and greenhouse gas emission reduction [12] are desired outcomes for the automotive industry, which can be achieved by improving the mechanical properties of the AHSSs [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Al increases the temperature range for intercritical annealing to higher temperatures [ 34 ]. This allows the annealing time to be reduced by enhancing the Mn diffusion without decreasing the stability of the retained austenite otherwise detectable at higher annealing temperatures [ 31 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%